The Herd Health Handbook for Goat Producers: Vaccination Protocol and Quality Assurance Measures for Goats - Ray Mobley; Carmen Lyttle-N’guessan; Thomas Peterson (EDIS)
FAMU004, a 9-page fact sheet by Ray Mobley, Carmen Lyttle-N'guessan, and Thomas Peterson, outlines a year-round preventive-based health maintenance program for goats, including schedules for vaccinations and anthelmintics, and common medications with approximate withdrawal times. Published by the Florida A & M University Extension, September 2009.